Equazioni di primo grado con frazioni
scarica il file  .DOC compresso in formato zip 


Equazione 1 (soluzione)

Equazione 2 (soluzione)

Equazione 3 (soluzione)

Equazione 4 (soluzione)


Soluzione 1

 

5 -10x +4 -4x = 2x -13 -8x +6
8x -10x -4x -2x = -13 +6 -5 -4
-8x = -16
8x = 16
x=2

Verifica 1

(1-4)/2+(4-8)/10=(4-13)/10-(8-3)/5
-3/2-4/10=-9/10-5/5
(-15-4)/10=(-9-10)/10
-19/10=-19/10
verificata 

Soluzione 2

 

1 modo

 

2 modo

  

Verifica 2

 

Soluzione 3


 

48x - 3x - 9 - 20x - 20 = 18x - 36 - 16x - 16
48x - 3x - 20x + 16x - 18x = - 36 - 16 + 9 + 20
23x=-23
x = -1

Verifica 

-4 - (2)/4 - [5 (0)]/3 = [3 ( 3)]/2 - [4 (0)]/3
-4 - 1/2 = - 9/2
(- 8 -1)/2 = - 9/2
- 9/2 = - 9/2
verificata 

Soluzione 4

 

10 (2x-1) - 15 (2-x) = 6 (x+1) + 12

20x - 10 -30 + 15x = 6x + 6 + 12

20x + 15x - 6x = 6 + 12 + 10 +30

29x = 58

x = 2

Verifica 4

verificata